1986
DOI: 10.1007/bf02555287
|View full text |Cite
|
Sign up to set email alerts
|

Bladder and sexual function after surgery for rectal cancer

Abstract: Bladder function and sexual potency were studied before and after surgery for rectal carcinoma. Urinary voiding after postoperative removal of indwelling catheter was impaired in seven of 22 men, leading to prostatic surgery in four. Two years later, eight of 16 men reported disturbed voiding, but no significant changes were found in bladder capacity, residual volume, flow rate, or detrusor pressure. Sexual potency was reduced in five of ten men, in one with retrograde ejaculation; and three did not achieve er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
2
3

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(27 citation statements)
references
References 21 publications
0
22
2
3
Order By: Relevance
“…Although a number of studies have addressed the issue of sexual dysfunction after rectal excision, most investigators have used self-made questionnaires [5][6][7][8][9][10][11][12][13]. The International Index of Erectile Function (IIEF), an internationally recognized, well-structured questionnaire for evaluating sexual function, has been used recently by relatively few studies dealing with the sexual dysfunction after rectal cancer surgery [4,[14][15][16][17][18].…”
mentioning
confidence: 99%
“…Although a number of studies have addressed the issue of sexual dysfunction after rectal excision, most investigators have used self-made questionnaires [5][6][7][8][9][10][11][12][13]. The International Index of Erectile Function (IIEF), an internationally recognized, well-structured questionnaire for evaluating sexual function, has been used recently by relatively few studies dealing with the sexual dysfunction after rectal cancer surgery [4,[14][15][16][17][18].…”
mentioning
confidence: 99%
“…Karanjia et al [75] reported that serious leakage after total mesorectal excision, defined as the need for emergency laparotomy for fecal peritonitis, actually occurred significantly more often in patients without than with diversion (8% vs. 1%). The incidence of urinary retention and sexual dysfunction in many studies did not appear to be higher after colo-anal anastomosis than after conventional anal low anterior resection [76,77].…”
Section: Complicationsmentioning
confidence: 98%
“…10,11 The fascia propria of the rectum is separated by an avascular plane from the sacral fascia, which lies more posteri- orly over the sacrum. These 2 fascia layers merge more distally, where the rectum turns more anteriorly 9 and the mesorectum ends 2 cm above the sphincter apparatus.…”
Section: P Artial or Total Excision Ofmentioning
confidence: 98%
“…For this reason, symptoms due to sympathetic denervation are much more common than those caused by parasympathetic injury. 9 Visual identification of the nerves can be accomplished if the anatomic planes are respected and the rectum is excised en bloc with its mesorectum.…”
Section: P Artial or Total Excision Ofmentioning
confidence: 99%